Relasi Pusat-Daerah dalam Paradiplomasi Bermotif Nasionalistik: Studi Perbandingan Kasus Skotlandia dan Papua - Anggi Koenjaini Putri; Dhania Aisyah Aurella; Nurul Azizah Salma; Ario Bimo Utomo (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
Abstract This research describes a comparison of the practice of paradiplomacy between Scotland and Papua with the main focus on analyzing the relationship between the central government and local government in the two regions. These two different regions have three characteristics in common, namely they both have problems of separatism, both are recognized as autonomous regions by the central government, and there are para-diplomacy activities. This research uses a qualitative method with the data obtained based on secondary data through the study of literature. The purpose of this research is to determine the tendency of cooperative or conflictual relationships in the relationship between the central government and local government in the two regions by referring to the theoretical basis of Panayotis Soldatos and David Criekemans. The results of the research explain that the relationship between the center and local government of the two regions has the same pattern and is influenced by the dynamics of the national movement and does not have the authority to regulate foreign relations. It is hoped that this research can be a reference for other writers in researching the practice of paradiplomacy with the background of the nationalism movement. Keywords: nationalism, Papua, paradiplomacy, Scotland Abstrak Penelitian ini menjelaskan tentang perbandingan praktik paradiplomasi antara Skotlandia dan Papua dengan fokus utama menganalisis hubungan pemerintah pusat dan pemerintah daerah di kedua wilayah. Dua wilayah yang berbeda ini memiliki tiga persamaan karakteristik yakni keduanya memiliki masalah separatisme, keduanya juga diakui sebagai daerah otonom oleh pemerintah pusat, dan terdapat aktivitas paradiplomasi. Penelitian ini menggunakan metode kualitatif dengan data-data yang diperoleh berdasarkan data sekunder melalui studi literatur. Tujuan dari penelitian ini untuk mengetahui kecenderungan hubungan yang kooperatif atau konfliktual dalam hubungan pemerintah pusat dan pemerintah daerah di kedua wilayah dengan mengacu pada dua landasan teori dari Panayotis Soldatos dan David Criekemans. Hasil penelitian menjelaskan bahwa hubungan pemerintah pusat dan pemerintah daerah di kedua wilayah memiliki pola yang sama dan dipengaruhi oleh dinamika gerakan nasional serta tidak memiliki wewenang dalam mengatur hubungan luar negeri. Diharapkan penelitian ini dapat menjadi referensi bagi penulis lain dalam meneliti pengelolaan praktik paradiplomasi yang berlatar belakang gerakan nasionalistik. Kata kunci : nasionalisme, Papua, paradiplomasi, Skotlandia